Optimal Patent Protection and Expected Utility Model: A Transition Economy Example - Ibrahim Niftiyev (Scientific Collection InterConf+: Proceedings of the 3th International Scientific and Practical Conference «Theory and Practice of Science: Key Aspects», Rome, Italy, May 21-22, 2021, 2021)
This paper aims to critically appraise optimal patent protection using the expected utility model from the perspectives of governments to balance the motivation and social use of the intellectual property. In order to achieve this aim, the report has presented the working mechanism of governments towards patent protection; use of utility model by governments; past and present academic investigations on the topic; strategizing behavior of governments towards patents and as a brief example, a case of the transition economy. The expected utility model has provided an effective and efficient framework for the development of patent strategy by governments. The essay has noted that due to the differences between industries and their dynamics, it is expected that diverse patent regimes should be followed to balance the social utility and economic utility of the economic actor to engage in research and development.
Keywords: 330; Patent protection; expected utility; function; optimization; transition economy